2016
DOI: 10.1111/cmi.12565
|View full text |Cite
|
Sign up to set email alerts
|

Subtilase cytotoxin produced by locus of enterocyte effacement‐negative Shiga‐toxigenic Escherichia coli induces stress granule formation

Abstract: Subtilase cytotoxin (SubAB) is mainly produced by locus of enterocyte effacement (LEE)-negative strains of Shiga-toxigenic Escherichia coli (STEC). SubAB cleaves an endoplasmic reticulum (ER) chaperone, BiP/Grp78, leading to induction of ER stress. This stress causes activation of ER stress sensor proteins and induction of caspase-dependent apoptosis. We found that SubAB induces stress granules (SG) in various cells. Aim of this study was to explore the mechanism by which SubAB induced SG formation. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 101 publications
0
34
0
Order By: Relevance
“…A recent study showed that SubAB induces stress granules in various cells in a PERK-dependent manner [ 22 ]. Furthermore, Halder et al reported that the Helicobacter pylori produced HP0175, a peptidyl-prolyl cis-trans isomerase, activates the PERK arm consequently leading to production of ATF4 and CHOP which both induce the expression of autophagy-related genes [ 23 ].…”
Section: The Role Of Individual Er Stress Marker Activationmentioning
confidence: 99%
“…A recent study showed that SubAB induces stress granules in various cells in a PERK-dependent manner [ 22 ]. Furthermore, Halder et al reported that the Helicobacter pylori produced HP0175, a peptidyl-prolyl cis-trans isomerase, activates the PERK arm consequently leading to production of ATF4 and CHOP which both induce the expression of autophagy-related genes [ 23 ].…”
Section: The Role Of Individual Er Stress Marker Activationmentioning
confidence: 99%
“…7,8) After translocation into ER via the trans-Golgi network (TGN), SubAB cleaves BiP, resulting in ER stressinduced cytotoxicity through activation of ER stress sensors, PERK, IRE1α and ATF6 signaling, which mediate a unique signaling pathway including phosphorylation of eIF2α and expression of C/EBP homologous protein (CHOP). 9,10) To date, several studies have demonstrated that SubAB induces cytotoxicity in vitro and lethal severe hemorrhagic inflammation in mice, inhibition of autophagy and stress granule formation. Our previous study demonstrated that SubAB inhibits LPSinduced nitric oxide (NO) production in macrophages through the suppression of nuclear factor-kappaB (NF-κB) activation and subsequent inducible NO synthase (iNOS) expression.…”
Section: Introductionmentioning
confidence: 99%
“…After SubAB binds to its surface receptors 6 8 , the toxin translocates into cells through clathrin-mediated 9 or lipid rafts- and actin-dependent pathways 10 and then cleaves at a specific site on the chaperone protein BiP/Grp78 in the endoplasmic reticulum (ER) 4 . BiP cleavage by SubAB causes ER stress, followed by activation of ER-stress sensor proteins (e.g., IRE1, ATF6, PERK) 11 , 12 , which initiate cell damage pathways 11 , 12 and various cell responses including inhibition of iNOS synthesis 13 and stress granule formation 14 . In addition, administration of SubAB to mice causes a lethal severe hemorrhagic inflammation, injury to intestinal cells, extensive microvascular thrombosis, evidence of histological damage in kidneys, and liver, and dramatic splenic atrophy 15 17 .…”
Section: Introductionmentioning
confidence: 99%